A CASE REPORT: ANTIRETROVIRAL-ASSOCIATED BILATERAL GYNECOMASTIA - Sidarta, Erdo Puncak; Syeben Hezer Epatah Hietingwati; Robertus Arian Datusanantyo (Universitas Airlangga, 2023)
Highlights: Gynecomastia is a known potential side effect of efavirenz, which may manifest in HIV patients. Healthcare providers should be vigilant and address the potential adverse effects of medications prescribed to individuals with HIV, including gynecomastia. Surgeons in resource-limited areas show flexibility and can achieve satisfactory results in procedures despite limited resources and surgical options. Abstract: Background: Human Immunodeficiency Virus (HIV) patients can now access antiretroviral drugs even in resource-limited area. The majority of patients receive the fixed daily dose of an efavirenz-based antiviral (ARV) as advised by the World Health Organization (WHO), despite the fact that gynecomastia is a recognized side effect of evafirenz. Case Ilustration: We report a 31 year-old male with antiretroviral-associated gynecomastia that underwent the bilateral excision without liposuction procedure with satisfying result. Discussion: Surgeon in limited-resource area faces limited resources to perform some specific procedure. Meanwhile, limited resources also poses patients avoidable adverse events in otherwise clinical setting. The antiretroviral-associated gynecomastia is unavoidable because limited regimen choice. Surgeon needs also to adjust the surgical option to achieve satisfying result without instrument complexities. Conclusion: We reported satisfying surgical outcome in antiretroviral-associated bilateral gynecomastia patient with limited clinical setting.